Reputation, Satisfaction of Zakat Distribution, and Service Quality as Determinant of Stakeholder Trust in Zakat Institutions - Zainal, Hafizah; Bakar, Azizi Abu; Saad, Ram Al Jaffri (International Journal of Economics and Financial Issues, 2016)
Zakat is one of the five basic pillars in Islam and it is obligatory to all Muslims. Zakat is a system that can alleviate poverty in order to decrease the gap among rich and poor. If zakat can be managed effectively, the collection of zakat can be maximized compared to income tax collection. Thus, this article is an early study proposing a research model to examine the factors that influence stakeholder trust in zakat institutions. This is due to the lack of previous studies about stakeholder trust in zakat perspective. An extensive literature review method was utilized to identify and analyze the relevant literature in order to propose the model. This paper is discussing three factors which are reputation, satisfaction of zakat distribution, and service quality. Theoretical and practical of the paper as well as suggestions for future research were also discussed. Keyword: trust, zakat institutions; reputation; satisfaction of zakat distribution; service quality. JEL Classifications: I3, O15